HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG ISPA DENGAN SIKAP IBU TENTANG PENCEGAHAN PENULARAN ISPA PADA BAYI USIA 0-12BULAN DI PUSKESMAS PANDAAN - Ainiyah, Nur; Handayani, Dwining (Unusa Press, 2017)
ISPA is a disease that often occurs in children, especially toddlers. One of the factors increasing cases of ISPA in Puskesmas Pandaan known from interviews, 8 out of 10 people do not understand about ISPA and the prevention it The purpose of this research was to determine the correlation between mother's knowledge on ISPA with attitude of the mother on the prevention of transmission of ISPA in babies ages 0-12 Months in Helath Public Pandaan. The research method is analytic correlation with a sample population of 84 and 30 at the health center Pandaan in mothers who have babies aged 0-12 months who suffer from respiratory diseases by purposive sampling technique. Collecting data using closed questionnaire. For analysis of Spearman Rank correlation calculation used by the 95% significance level (α ≤ 0.05), if α ≤ 0.05, Hi accepted. The result showed the level of knowledge of mothers about ISPA either by 46.67% of respondents, the remaining 26.67% of respondents sufficient and less. The attitude of mothers on prevention of transmission ISPA is good by 46.67% of respondents, and the rest is not a good 40% of respondents and 13.33% of respondents to the attitude is not very good, and r count> r table (0.365> 0.364) with α of 0.05. Then there is a significant relationship between the level of knowledge of mothers about ISPA with transmission prevention in infants aged 0-12 months, because with knowledge and a good attitude will have an impact on healthy behaviors. With good knowledge and attitudes expected of a mother ISPA transmission in infants aged 0-12 months in particular can be prevented by following a health education and consultation with health workers in order to avoid further complications